Modeling of tungsten melt layer erosion caused by JxB force at TEXTOR with the code MEMOS - Bazylev, B.; Coenen, J.W. (Вопросы атомной науки и техники, 2013)
Tungsten in form of macrobrush is foreseen as one of candidate materials for the ITER divertor. Melting of tungsten, the melt motion, and melt splashing are expected to be the main mechanisms of a surface damage determining the lifetime of plasma facing components. Experiments with the long-time plasma action at the metalic surface in a strong magnetic field demonstrated that the JxB force generated by the thermo-emission electrons dominates in the acceleration of the melt layer and leads to a high target damage. In the paper numerical simulation model implemented into the code MEMOS is described and modelling of tungsten target damage caused by the long-time plasma heat loads supporting the TEXTOR experiments are performed with 3D version of the code MEMOS. Calculated damages of tungsten targets are in a reasonable agreement with the target damages observed in the TEXTOR experiments that allows projections upon the surface damage at ITER and DEMO conditions.